Apheresis in high risk antiphospholipid syndrome pregnancy and autoimmune congenital heart block. Issue 3 (December 2015) - Ruffatti, Amelia; Favaro, Maria; Brucato, Antonio; Ramoni, Veronique; Facchinetti, Myriam; Tonello, Marta; Del Ross, Teresa; Calligaro, Antonia; Hoxha, Ariela; Grava, Chiara; De Silvestro, Giustina
Abstract: In the first part a prospective cohort study was reported to evaluate the efficacy and safety of a treatment protocol including plasma exchange (PE) or PE plus intravenous immunoglobulins (IVIG) or immunoadsorption (IA) plus IVIG administered in addition to conventional therapy to 22 pregnant women with high-risk APS. The results indicate that PE or IA treatments administered along with IVIG and conventional antithrombotic therapy could be a valuable and safe therapeutic option in pregnant APS women with triple antiphospholipid antibody positivity along with a history of thrombosis and/or one or more severe pregnancy complications. In the second part the efficacy and safety of PE combined with IVIG and steroids were evaluated for the treatment of 10 patients with autoimmune congenital heart block (CHB) by comparing maternal features, pregnancy outcome and side effects with those of 24 CHB patients treated with steroids only. The patients treated with the combined therapy showed a statistically significant regression of 2nd degree blocks, an increase in heart rate at birth and a significantly lower prevalence of pacing in the first year of life. Moreover, no side effects were observed except for a few steroid-related events. If these results are confirmed by large-scale studies, the apheretic procedures could lead to improved outcomes in the treatment of these devastating diseases.